Rheumatoid arthritis patients are not at increased risk for 30-day cardiovascular events, infections, or mortality after total joint arthroplasty - Michaud, Kaleb (BioMed Central, 2013)
INTRODUCTION: Serious infection, cardiovascular disease, and mortality are increased in rheumatoid arthritis (RA). Whether RA affects the risk for these complications after total joint arthroplasty (TJA) is unknown, we hypothesize that it does. We compared the occurrence of 30-day postoperative complications and mortality in a large cohort of RA and osteoarthritis (OA) patients undergoing hip or knee TJA. METHODS: Analyses included 7-year data from the Veterans Affairs Surgical Quality Improvement Program. The 30-day complications were compared by diagnosis by using logistic regression, and long-term mortality was examined by using Cox proportional hazards regression. All analyses were adjusted for age, sex, and clustering by surgical site. Additional covariates included sociodemographics, comorbidities, health behaviors, and operative risk factors. RESULTS: The 34,524 patients (839 RA, 33,685 OA) underwent knee (65.9%) or hip TJA. Patients were 95.7% men with a mean (SD) age of 64.4 (10.7) years and had 3,764 deaths over a mean follow-up of 3.7 (2.3) years. Compared with OA patients, those with RA were significantly more likely to require a return to the operating room (odds ratio (OR), 1.45 (95% CI, 1.08 to 1.94), but had similar rates of 30-day postoperative infection, OR 1.02 (0.72 to 1.47), cardiovascular events, OR 0.69 (0.37 to 1.28), and mortality, OR 0.94 (0.38 to 2.33). RA was associated with a significantly higher long-term mortality; hazard ratio (HR), 1.22 (1.00 to 1.49). CONCLUSION: In this study of US veterans, RA patients were not at an increased risk for short-term mortality or other major complications after TJA, although they returned to the operating room more often and had increased long-term mortality.